Do analysts add value when they most can? Evidence from corporate spin‐offs - Feldman, Emilie R.; Gilson, Stuart C.; Villalonga, Belén (Strategic Management Journal, 2014)
This article investigates how securities analysts help investors understand the value of diversification. By studying the research that analysts produce about companies that have announced corporate spin‐offs, we gain unique insights into how analysts portray diversified firms to the investment community. We find that while analysts' research about these companies is associated with improved forecast accuracy, the value of their research about the spun‐off subsidiaries is more limited. For both diversified firms and their spun‐off subsidiaries, analysts' research is more valuable when information asymmetry between the management of these entities and investors is higher. These findings contribute to the corporate strategy literature by shedding light on the roots of the diversification discount and by showing how analysts' research enables investors to overcome asymmetric information . Copyright © 2013 John Wiley & Sons, Ltd.